Cooperative Law Policy: Historical Study Of Cooperative Settings In Indonesia - Cinantya Kumaratih; Tulus Sartono (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2020)
The existence of cooperatives has an important meaning for the welfare state of Indonesia. As a nation that was colonized for a long time, cooperatives as one of the implementations of a people's economy became a systematic effort to correct the economic structure of a colonial style. In this study examines the legal policies of cooperative arrangements from various eras in Indonesia. This research is normative legal research with secondary data. This research shows that the existence and development of cooperatives experience ups and downs in their legal policies. The colonial period of cooperative arrangements merely regulates cooperatives in existence and makes cooperatives one of the business actors. During the independence period, the aim of cooperatives was as a people's economic movement which was expected to be able to equalize welfare. Unfortunately, cooperatives in the old and new order regimes were used as political tools to perpetuate government power. During the reform period, the regulation of cooperatives was getting worse because it made cooperatives like companies pursuing mere profits.